Balancing student/trainee learning with the delivery of patient care in the healthcare workplace: a protocol for realist synthesis. Issue 4 (26th April 2016) - Sholl, Sarah; Ajjawi, Rola; Allbutt, Helen; Butler, Jane; Jindal-Snape, Divya; Morrison, Jill; Rees, Charlotte
Abstract : Introduction: A national survey was recently conducted to explore medical education research priorities in Scotland. The identified themes and underlying priority areas can be linked to current medical education drivers in the UK. The top priority area rated by stakeholders was: 'Understanding how to balance service and training conflicts'. Despite its perceived importance, a preliminary scoping exercise revealed the least activity with respect to published literature reviews. This protocol has therefore been developed so as to understand how patient care, other service demands and student/trainee learning can be simultaneously facilitated within the healthcare workplace. The review will identify key interventions designed to balance patient care and student/trainee learning, to understand how and why such interventions produce their effects. Our research questions seek to address how identified interventions enable balanced patient care-trainee learning within the healthcare workplace, for whom, why and under what circumstances. Methods and analysis: Pawson's five stages for undertaking a realist review underpin this protocol. These stages may progress in a non-linear fashion due to the iterative nature of the review process. We will: (1) clarify the scope of the review, identifying relevant interventions and existing programme theories, understanding how interventions act to produce their intended outcomes; (2) search journal articles and grey literature for empirical evidence from 1998 (introduction of the European Working Time Directive) on the UK multidisciplinary team working concerning these interventions, theories and outcomes, using databases such as ERIC, Scopus and CINAHL; (3) assess study quality; (4) extract data; and (5) synthesise data, drawing conclusions. Ethics and dissemination: A formal ethical review is not required. These findings should provide an important understanding of how workplace-based interventions influence the balance of trainee learning and service provision. They should benefit various stakeholders involved in workplace-based learning interventions, and inform the medical education research agenda in the UK.